Judgment of emotional information expressed by prosody and semantics in patients with unipolar depression - Schlipf, Sarah; Batra, Anil; Walter, Gudrun; Zeep, Christina; Wildgruber, Dirk; Fallgatter, Andreas J.; Ethofer, Thomas (Frontiers in Psychology, 2013)
It was the aim of this study to investigate the impact of major depressive disorder (MDD) on judgment of emotions expressed at the verbal (semantic content) and non-verbal (prosody) level and to assess whether evaluation of verbal content correlate with self-ratings of depression-related symptoms as assessed by Beck Depression Inventory (BDI). We presented positive, neutral, and negative words spoken in happy, neutral, and angry prosody to 23 MDD patients and 22 healthy controls (HC) matched for age, sex, and education. Participants rated the valence of semantic content or prosody on a 9-point scale. MDD patients attributed significantly less intense ratings to positive words and happy prosody than HC. For judgment of words, this difference correlated significantly with BDI scores. No such correlation was found for prosody perception. MDD patients exhibited attenuated processing of positive information which generalized across verbal and non-verbal channels. These findings indicate that MDD is characterized by impairments of positive rather than negative emotional processing, a finding which could influence future psychotherapeutic strategies as well as provide straightforward hypotheses for neuroimaging studies investigating the neurobiological correlates of impaired emotional perception in MDD.